Access and acceptability of community‐based services for older Greek migrants in Australia: user and provider perspectives. (25th September 2012) - Hurley, Catherine; Panagiotopoulos, Georgia; Tsianikas, Michael; Newman, Lareen; Walker, Ruth
Abstract: In most developed nations, ageing migrants represent a growing proportion of the older population. Policies that emphasise care in the community depend on older migrants having access to formal services along with informal support, yet little is known about how older migrants experience community‐based formal services. By examining the views of both Greek elders in Australia and those of formal service providers, this research fills an important gap in the literature around access to and acceptability of formal community‐based services for older migrants. A research team including two Greek background researchers used existing social groups and a snowball sampling method to conduct face‐to‐face interviews and focus groups with seventy older Greeks in Adelaide, Australia. In addition, 22 community‐based service providers were interviewed over the telephone. Results from users and providers showed that while many older Greeks experience service access issues, they also relied heavily on family for support and assistance at home. Reliance on family was both in preference to formal services or where formal services were used, to locate, negotiate and monitor such services. Common barriers identified by both groups included cost, transport and availability, but additional challenges were posed by language, literacy and cultural attitudes. Demographic changes including greater employment mobility and female workforce participation among adult children will have implications for both formal and informal care providers. Formal service providers need to ensure that services are promoted and delivered to take account of the important role of family in informal support while also addressing the access challenges posed by language and literacy. Research conducted by researchers from the same cultural background in the respondent's native language can further advance knowledge in this area.